Mechanical drilling processes for titanium alloys: a literature review - Zhang, Pengfei; Churi, N. J.; Pei, Zhijian J.; Treadwell, C. (My University, 2008)
Titanium and its alloys (Ti) are attractive for many applications due to their superior properties. However, they are regarded as hard-to-machine materials. Drilling is an important machining process since it is involved in nearly all Ti applications. It is desirable to develop cost-effective drilling processes for Ti and/or improve the cost-effectiveness of currently-available processes. Such development and improvement will be benefited by a comprehensive literature review of drilling processes for Ti. This paper presents a literature review on mechanical drilling processes for Ti, namely, twist drilling, vibration assisted twist drilling, ultrasonic machining, and rotary ultrasonic machining. It discusses cutting force, cutting temperature, tool wear and tool life, hole quality (diameter and cylindricity, surface roughness, and burr), and chip type when drilling of Ti using these processes.
Keywords: Cutting force; Drilling; Machining; Surface roughness; Titanium alloy; Tool wear